Advanced Oxidation Processes for Water Treatment: A Comprehensive Review - Cardoso, Inês; Muruganandham, Andrea; Capodaglio, Tigi; Alaton, Idil; Silva, Luís (Journal of Functional Materials and Applied Engineering, 2024)
Stubborn trace organics—so-called micropollutants—are steadily tainting water bodies, endangering both ecosystems and public health. Because classic treatment trains scarcely touch these compounds, next-generation removal technologies are urgently needed. Advanced Oxidation Processes (AOPs) have stepped to the forefront as a potent counter-strategy. They produce, in situ, an arsenal of indiscriminate •OH and other ROS that rapidly dismantle trace organics, driving them toward innocuous products or full mineralization. This review delivers an integrated roadmap to AOP fundamentals, reaction pathways, and typologies—spanning ozone, H₂O₂, photocatalytic, sonochemical, and electrochemical variants. The application of AOPs in water treatment is critically examined, with specific examples from scientific literature illustrating their efficacy against pharmaceuticals, pesticides, and industrial chemicals. Finally, the review discusses the current challenges, such as energy consumption, formation of toxic by-products, and operational costs, and outlines promising future research directions, including the development of novel catalysts, hybrid systems, energy-efficient reactor designs, and process control strategies for full-scale implementation.